Damage Assessment of an RC Pier under Noncontact Blast Loading Based on P-I Curves - Lu Liu; Zhouhong Zong; Biao Tang; Minghong Li (Shock and Vibration)
Since the 9.11 attacks in New York, terrorist attacks, military strikes, and accidental explosions have caused serious damage to various infrastructures around the world. Accidental traffic explosions in bridge engineering have occurred frequently due to the increasing firework truck on the bridge and heavy fuel oil ships under the bridge. Besides, intentional car bomb explosions in terrorist attacks and military assaults are significant threats to the bridge structure. Bridge pier is a particularly important component of the overall bridge structure due to its vertical support capacity. Therefore, the damage of reinforced concrete (RC) piers under blast loading should be studied. In this paper, the pier is simplified as a single degree of freedom (SDOF) system based on energy equality, and the blast loading distribution on the surface of the pier is simplified as a uniform distribution. Then, the P-I curves of an RC pier are obtained based on the SDOF system and a uniform distribution blast loading to quickly evaluate the damage extent of an RC pier so that the P-I curves and fitting formulas for different damage extents can be used for practical engineering. After a numerical simulation verification, the P-I curves and fitting formulas based on the simplified method can supply a rapid and effective method for engineers to assess the postexplosive damage of an RC pier.